Mediating role of social support on the relationship between stress and quality of life among mothers of children with Thalassemia in Malaysia - Abdul Halim, Hazlina; Juhari, Rumaya; Yaacob, Siti Nor (Community Health Society Malaysia, 2017)
Background: Mothers of Thalassemia children are often confronted with stressful life associated with the illness of the child as well as other related stressors. Consequently, these mothers’ quality of life is impacted. Past studies have shown that perceived social support is a part of coping strategies that can help mothers to cope with their stressful life and increase their health status. Materials and Methods: This is a cross-sectional study involving 372 mothers whose children suffer from Thalassemia with routine monthly blood transfusions treatment from ten government hospitals in Malaysia. Data collection consisted of face-to-face interviews using Parental Stress Scale, Multidimensional Scale of Perceived Social Support and SF 12v2 measuring the respective variables. Medical Research Ethics Committee (MREC) ethical approval was obtained prior to conduct this study. Result: Findings indicated significant negative direction in relationships between stress and social support and between stress and quality of life. Besides that, the relationship between social support and quality of life showed significant positive direction. Results also showed that when controlling for the mediating variable, stress has the strongest significant influence on quality of life (β = - 8.292, p < 0.001) and confirmed that social support is significantly mediating that relationship. Conclusion: In sum, the findings from our study highlight the importance of social support perceived by mothers in buffering the effect of stress on their quality of life. It should be of concern of many on the issues and challenges that are faced by mothers of Thalassemia children as the primary caregiver.